Pengaruh Model Personalized System For Intruction Dalam Pembelajaran Pencak Silat Terhadap Minat Belajar Siswa Sekolah Menengah Atas - Inggit Sri Garnasih; Ega Trisna Rahayu; Rizki Aminudin (Peneliti.net, 2021)
The purpose of this study was to determine, analyze, and identify the effect of the Personalized System for Instruction Model in Pencak Silat Learning on Student Interest in SMAN 1 Banyusari. To respond to the formulation of the research problem that has been formulated, the author uses a quantitative approach with an experimental method. This research was conducted at SMAN 1 Banyusari by taking one class as the research sample, namely X-MIPA 1 with 31 students out of 141 students from the total X class of 5 classes. There are three stages in this study, namely pretest, treatment, and posttest. Pretest was conducted to determine the initial interest in students' learning before getting treatment. After the pretest, the researcher gave treatment, namely eight meetings using the Personalized System For Instruction model. The technique used to analyze the data is using the paired T-test. There is a significance value (2-tailed) of 0.000, so the significance value (2-tailed) > 0.05, it can be concluded that the Personalized System For Instruction model in learning pencak silat has an influence on student interest in SMAN 1 Banyusari.